Supporting COVID-19 policy-making with a predictive epidemiological multi-model warning system - Martin Bicher; Martin Zuba; Lukas Rainer; Florian Bachner; Claire Rippinger; Herwig Ostermann; Nikolas Popper; Stefan Thurner; Peter Klimek (Communications Medicine, 2022)
Bicher, Zuba et al. consolidate the output of three epidemiological models to perform weekly forecasts of COVID-19 cases and required hospital beds. The predictions are more accurate than the individual models and enable planning of health care and COVID-19 interventions by national decision-makers.